Paths to Parenthood Emotions on the Journey through Pregnancy, Childbirth, and Early Parenting (Springer Singapore, 2018)
This interdisciplinary book explores the affective dimensions of becoming a parent, traversing the life-cycle journey of pregnancy, childbirth, and early parenting. Bringing together researchers from sociology, history, feminist studies, cultural studies, general medicine, and psychiatry, Paths to Parenthood analyses rich narratives that represent a diverse cross-section of parents, including migrants, same-sex couples, and single parents.